2001
DOI: 10.1007/s004970000062
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a polygalacturonase enzyme in germinating pollen of Brassica napus

Abstract: Penetration of pollen tubes through stigmatic tissues in Brassica napus L. may involve the release of cell wall modifying enzymes from the pollen tube tip. We have examined the expression of a pectin-degrading polygalacturonase (PG) enzyme in unpollinated and early and late pollinated stigmas via immunoblotting and immuno light microscopy using a PG polyclonal antibody. Immunoblotting analysis indicated that PG enzyme was present at low levels in unpollinated stigmas and at high levels in pollinated stigmas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…Tube growth seems to be facilitated by wall-degrading enzymes produced either by the pollen itself or by the stigma. This is in agreement with the finding that group I allergens of grass pollen have expansin activity (Cosgrove et al, 1997) and that a polygalacturonase was localized in Brassica germinating pollen (Dearnaley and Daggard, 2001, and references therein). In tobacco, a species with a wet stigma and a solid style, pollen tubes grow through the intercellular spaces between the cells of the secretory zone, within the exudate produced by these cells.…”
Section: Pollen-stigma Interactionssupporting
confidence: 92%
“…Tube growth seems to be facilitated by wall-degrading enzymes produced either by the pollen itself or by the stigma. This is in agreement with the finding that group I allergens of grass pollen have expansin activity (Cosgrove et al, 1997) and that a polygalacturonase was localized in Brassica germinating pollen (Dearnaley and Daggard, 2001, and references therein). In tobacco, a species with a wet stigma and a solid style, pollen tubes grow through the intercellular spaces between the cells of the secretory zone, within the exudate produced by these cells.…”
Section: Pollen-stigma Interactionssupporting
confidence: 92%
“…A semiquantitative RT-PCR analysis investigating 66 among the 69 genes coding for PGases showed that 32 genes were strongly expressed in flower tissues (Kim et al, 2006). Other studies also have shown that PGases were present in ungerminated pollen grains of Brassica napus (Dearnaley and Daggard, 2001) and during hydration of Platanus acerifolia pollen grains (Suárez-Cervera et al, 2005). In addition, in Brassica campestris, alteration of the expression of B. campestris MALE FERTILITY2 (coding for a putative PGase) resulted in an overdeveloped intine and abnormal germination (Huang et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Hydrolysis of pectin in the stigma cell wall also is necessary, for which pollen expresses genes encoding pectin esterase and pectate lyase (Kim et al, 1996;Wu et al, 1996). A pollen-specific Brassica polygalacturonase also has been detected at the tip of pollen tubes as they enter the stigma papillar cell walls (Dearnaley and Daggard, 2001).…”
Section: Pollen Tube Invasion: Growing Into the Stigmamentioning
confidence: 99%